MAKNA TRADISI UANG PANAI DALAM ADAT PERNIKAHAN SUKU BUGIS DI SUNGAI GUNTUNG KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Widyawati "; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
panai is money given by the groom to the family of the bride. Money panaiis intended for shopping wedding. Money panai has a very important role and is one ofthe pillars in the customary marriage of the Bugis tribe, especially in the community ofSungai Guntung Kecamatan Kateman District Indragiri Hilir Provinsi Riau. The purposeof this research is to see the meaning of traditions of cash money in middle and uppermiddle to middle bussiness community in Sungai Guntung Kateman District, want toknow the meaning of symbols contained in traditions of cash money, and the valuescontained in traditions of cash money on people Bugis tribe in Sungai Guntung DistrictsKateman regency Indragiri Hilir Provinsi Riau.The method of this research is qualitative, data collection techniques useobeservation, interview and documentation. In-depth interviews were conducted with theinformens of this research are Customary, Tradisional and Community Traders, usingthe snowball method of collecting data starting from several people who meet the criteriato be a member of the sample. To confirm the validity of this research data is done throughextension of participation and triangulation of data.The results of this indicate that the meaning of tradisions of cash monay in SungaiGuntung Kateman District is a cultural core, where a difficult to change. Currency moneypanai to give prestige for the family of women if the amount of money panai’ which inpeg is able to be met by the prospective groom. In terms of its function of money panai isa gift for the bride as the cost of a wedding reception. The value of cash money is largelydetermined by the status of social status of women in society, such as educatoin, familyeconomy, physical perfection, job title and descent. In addition to the money in the panaitradition is also aquipped with various equipment symbols such as rice, ginger andturmeric, a piece of cloth, wood, needles, betel, and cinnamon. Of the attributes of theaccompaniment of the cash money symbolizes the life of the household of the Bugis tribehaving certain meanings.